STRATEGI KOMUNIKASI ORANG TUA DALAM MENGENALKAN ASPEK SOSIAL PADA ANAK USIA 5-6 TAHUN DI KELURAHAN FAOBATA - Yasina Ture; Yasinta Maria Fono; Marsianus Meka; Elisabeth Tantiana Ngura (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze parental communication strategies in introducing social aspects to children aged 5-6 years in Faobata Village and see the correlation with children's social performance at school. The research uses a qualitative approach with a descriptive method. Data were obtained through in-depth interviews with three parents and one kindergarten teacher, as well as observations of communication practices in daily life. The results of the study show that parents' communication strategies are divided into two main forms, namely verbal and nonverbal communication. Verbal communication is carried out through inductive reasoning, simple advice, and positive reinforcement in the form of praise. This strategy helps children understand the cause-and-effect relationship in social behavior so that the obedience formed is conscious and rational. Meanwhile, nonverbal communication such as hugs, facial expressions, touch, and eye gestures play a role in building emotional regulation and secure attachment between parents and children. Habituation and example are the main instruments in internalizing social values. This study also found a strong correlation between home parenting and children's social performance at school. Children who receive emotional attention and consistent communication at home show better ability to share, cooperate, and resolve conflicts in the school environment. In addition, the sociocultural values of the Bajawa people also strengthen the process of social education in the family.